2007
DOI: 10.3748/wjg.v13.i4.619
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of partial splenic embolization on platelet values for liver cirrhosis patients with thrombocytopenia

Abstract: AIM:To investigate the effect of partial splenic embolization (PSE) on platelet values in liver cirrhosis patients with thrombocytopenia and to determine the effective embolization area for platelet values improvement. METHODS:Blood parameters and liver function indicators were measured on 10 liver cirrhosis patients (6 in Child-Pugh grade A and 4 in grade B) with thrombocytopenia (platelet values < 80 × 10 3 /μL) before embolization. Computed tomography scan was also needed in advance to acquire the splenic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 22 publications
1
47
0
Order By: Relevance
“…We performed a review of the English language literature for PSE and focused on papers from 2005 through the present. Ultimately, eight studies were identified, and have been included in our review ( Table 1) [9,[11][12][13][14][15][16][17] . In 2012, Smith et al [18] also published an excellent review of splenic artery embolization, which followed a similar structure.…”
Section: Outcomes Of Psementioning
confidence: 99%
See 1 more Smart Citation
“…We performed a review of the English language literature for PSE and focused on papers from 2005 through the present. Ultimately, eight studies were identified, and have been included in our review ( Table 1) [9,[11][12][13][14][15][16][17] . In 2012, Smith et al [18] also published an excellent review of splenic artery embolization, which followed a similar structure.…”
Section: Outcomes Of Psementioning
confidence: 99%
“…Over the past decade the use of PSE to increase platelet counts has facilitated antiviral treatment in patients who would have otherwise been too thrombocytopenic. Tahara completed a retro- Kim et al [11] 2012 South Korea Case series report Elmonem et al [12] 2010 Egypt Case series report Zhu et al [14] 2009 China Nonrandomized prospective trial Amin et al [9] 2009 Egypt Zhu et al [16] 2008 China Hayashi et al [17] 2007 Japan Nonrandomized Lee et al [15] 2007 China Nonrandomized [13] 2005 France ing episodes from 4.3 prior to treatment to 1.1 after PSE.…”
Section: Hematologic Indicesmentioning
confidence: 99%
“…An alternative approach is partial or total embolization of the splenic artery, which, in some recent studies, has been associated with good results, in particular, lower morbidity and mor tality rates than those associated with surgery. Partial embolization preserves the immunological function of the spleen and is the preferred option for patients with cirrhosis [10] .…”
Section: Portal Hypertension and Anemiamentioning
confidence: 99%
“…In this study, embolization ranged from 50% to 70%. Lee et al [23] reported that there are significant differences in platelet values between low and high embolization areas in patients with cirrhosis. The complication rate for < 30% and > or = 30% embolization areas is 50% and 100%, respectively.…”
Section: Discussionmentioning
confidence: 99%